The Concept of an Economic Quantity - Carver, T. N. (Quarterly Journal of Economics, 1907)
Journal Article The Concept of an Economic Quantity Get access T. N. Carver T. N. Carver Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 21, Issue 3, May 1907, Pages 427–448, https://doi.org/10.2307/1884906 Published: 01 May 1907